2005
DOI: 10.1016/j.clpt.2004.12.206
|View full text |Cite
|
Sign up to set email alerts
|

No effect of concomitant administration of nebivolol and losartan in healthy volunteers genotyped for CYP2D6 status

Abstract: Background Nebivolol (N) has been shown through a number of studies to be a cardioselective β1‐antagonist with vascular endothelial nitric oxide releasing capabilities that exhibits CYP2D6‐mediated polymorphic metabolism. Losartan (L), an ARB, is extensively metabolized by CYP2C9 (a known polymorphic enzyme) and is likely to be used concomitantly. This study examined if co‐administration of N and L alters the pharmacokinetic (PK) characteristics of either agent, or the active metabolite of L, EXP‐3174. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A study (n = 24) of the coadministration of single doses of nebivolol 10 mg and losartan 50 mg, an angiotensin II receptor blocker that is extensively metabolized by CYP2C9 (a known polymorphic enzyme), found that neither agent had any effect on the pharmacokinetics of the other drug in either EM or PM subjects 58 . In other studies, no drug interactions affecting the pharmacokinetics of either agent were reported with coadministration of nebivolol and the ACE inhibitor ramipril or the diuretic furosemide 59 , 60 .…”
Section: Nebivolol: a Novel Vasodilating β‐Blockermentioning
confidence: 99%
“…A study (n = 24) of the coadministration of single doses of nebivolol 10 mg and losartan 50 mg, an angiotensin II receptor blocker that is extensively metabolized by CYP2C9 (a known polymorphic enzyme), found that neither agent had any effect on the pharmacokinetics of the other drug in either EM or PM subjects 58 . In other studies, no drug interactions affecting the pharmacokinetics of either agent were reported with coadministration of nebivolol and the ACE inhibitor ramipril or the diuretic furosemide 59 , 60 .…”
Section: Nebivolol: a Novel Vasodilating β‐Blockermentioning
confidence: 99%
“…[63][64][65][66][67][68][69][70] However, 3-fold increases in nebivolol peak plasma concentrations and 8-fold increases in area under the curve occur during concomitant administration with fluoxetine, a known CYP2D6 inhibitor, and therefore caution should be exercised when administering nebivolol and any CYP2D6 inhibitor in hypertensive patients. 71 Given the negative chronotropic and inotropic properties and the antihypertensive effects of nebivolol, it is likely that a pharmacodynamic interaction may exist between nebivolol and other agents with similar properties.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…The FDA has recommended screened designs for CYP2D6-, CYP2C19-, or CYP2C9-mediated drug-drug interaction studies (FDA, 2004a). Several companies have reported results from such studies (Lawrence et al, 2005;Li et al, 2005;Small et al, 2005). Selected clinical trials ( Fig.…”
Section: Genetics As An Element Of Clinical Trial Designmentioning
confidence: 99%